The PhD viva: a space for academic development. Issue 3 (2nd July 2016) - Share, Michelle
Abstract : This study examined the viva experiences of 87 social science PhD graduates from three Irish higher education institutions through a questionnaire that assessed outcome, preparation, conduct and post-viva. The majority were awarded their PhD with minor corrections, considered their viva as a summative assessment, and emphasised its purpose as authentication, examination and defence. Most felt well prepared yet few had experienced a 'mock viva' or viva workshop. Even those with minor corrections identified aspects of the viva for improvement. The study recommends that academic development programmes should incorporate assessment literacy for PhD students and supervisors and the need for evaluation of graduates' viva experiences.